2020
DOI: 10.1158/2159-8290.cd-19-0435
|View full text |Cite
|
Sign up to set email alerts
|

MYC Instructs and Maintains Pancreatic Adenocarcinoma Phenotype

Abstract: The signature features of pancreatic ductal adenocarcinoma (PDAC) are its fibroinflammatory stroma, poor immune activity and dismal prognosis. We show that acute activation of Myc in indolent PanIN epithelial cells in vivo is, alone, sufficient to trigger immediate release of instructive signals that together coordinate changes in multiple stromal and immune cell types and trigger transition to pancreatic adenocarcinomas that share all the characteristic stromal features of their spontaneous human counterpart.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 123 publications
6
115
0
Order By: Relevance
“…More recently and in the same line of reasoning, Omomyc expression in PDAC-bearing mice (pdx1-Cre;LSL-KRas G12D ;p53ER TAM ;TRE-Omomyc;CMV-rtTA) was shown to trigger quantitative regression of these highly aggressive tumors and of their extensive fibroinflammatory stroma (Figure 2), reiterating the point that Myc holds a key role in the coordination of the cross-talk between tumors and their microenvironment [72].…”
Section: Omomyc Efficacy and Side Effects In Vivomentioning
confidence: 59%
See 1 more Smart Citation
“…More recently and in the same line of reasoning, Omomyc expression in PDAC-bearing mice (pdx1-Cre;LSL-KRas G12D ;p53ER TAM ;TRE-Omomyc;CMV-rtTA) was shown to trigger quantitative regression of these highly aggressive tumors and of their extensive fibroinflammatory stroma (Figure 2), reiterating the point that Myc holds a key role in the coordination of the cross-talk between tumors and their microenvironment [72].…”
Section: Omomyc Efficacy and Side Effects In Vivomentioning
confidence: 59%
“…Expression of the Omomyc transgene has remarkable therapeutic impact in 5 different genetically engineered mouse models of cancer, from left to right: papilloma, inv-Myc-ER TAM (top panel) and inv-Myc-ER TAM /Omomyc (bottom panel), adapted from [56]; insulinoma, RIP1-Tag2;TRE-Omomyc;CMV-rtTA -dox (top) and +dox (bottom), adapted from [70]; lung adenocarcinoma, LSL-Kras G12D ;p53ER TAM ;TRE-Omomyc;CMV-rtTA -dox (top) and +dox (bottom), adapted from [71]; glioma, GFAP-V12 Ha-Ras;TRE-Omomyc;CMV-rtTA -dox (top) and +dox (bottom) adapted from[67]; and pancreatic ductal adenocarcinoma, pdx1-Cre;LSL-KRas G12D ;p53ER TAM ;TRE-Omomyc;CMV-rtTA -dox (top) and +dox (bottom), adapted from[72]. All panels represent tissue sections stained with either an anti-GFAP antibody (glioma) or with hematoxylin and eosin (rest of the panels).…”
mentioning
confidence: 99%
“…As fibroblasts evolved in part to facilitate wound repair, this may reflect a conserved mechanism by which mesenchymal cells signal to the epithelial compartment to promote regeneration and healing, as MYC has been previously implicated in the wound-healing process (Schäfer and Werner, 2007;Su et al, 2018;Zanet et al, 2005), as have MYC-regulated bioenergetics (Shyh-Chang et al, 2013). While previous studies have demonstrated a critical role for MYC in regulation of the tumor microenvironment (Kortlever et al, 2017;Sodir et al, 2011Sodir et al, , 2020, our findings suggest the existence of a feedback loop, in which cues from the fibroinflammatory microenvironment in turn augment MYC protein level and oncogenic activity. As PDAC rarely harbors PI-3K mutations (Cancer Genome Atlas Research Network, 2017), it was not entirely surprising that external signals can increase AKT phosphorylation in PDAC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the status of the RAS-MYC oncogenic axis is important for the regenerative program, which is involved in PDAC initiation, 22,23 we investigated whether the RAS-MYC oncogenic axis is altered in KCS mice. We found that the expression of c-Myc expression was significantly decreased in KCS mice compared to control mice ( Supplementary Figure 8).…”
Section: Suppression Of Pancreatic Ductal Adenocarcinoma Formation Bymentioning
confidence: 99%